The Influence of the Utilization of Learning Technology on the Learning Motivation of Students majoring in Office Administration and Business Services - Restu Qurniawati; Jamaluddin Jamaluddin; Sitti Hardiyanti Arhas (International Journal of Administration and Education (IJAE), 2026)
The integration of technology in the learning process constitutes a significant factor contributing to the enhancement of students’ learning motivation. This study aims to examine the effect of learning technology utilization on the motivation of students enrolled in the Office Management and Business Services (MPLB) program at SMK Negeri 1 Bantaeng. Employing a quantitative approach with descriptive and inferential methods, data were collected through questionnaires, interviews, and documentation, with 152 respondents selected from a population of 250 students using a simple random sampling technique. The results show a positive and statistically significant link between using learning technology and students' motivation. This is shown by a correlation coefficient of 0.554, which is in the moderate range, and a coefficient of determination (R Square) of 0.306, which means that 30.6% of the change in learning motivation is due to technology use, while the other 69.4% is due to other factors that are not covered in this study. Additionally, the level of technology utilization in learning is categorized as satisfactory, achieving 57% based on indicators such as message delivery, instructional strategies, and implementation forms, while students’ learning motivation is also classified as excellent with a percentage of 64% derived from intrinsic and extrinsic motivational aspects. These findings imply that, although not the sole determinant, technology plays a substantial role in fostering active student engagement; therefore, optimizing its use in the learning process provides greater opportunities to enhance motivation, and teachers are expected to design technology-based learning that is creative, interactive, and aligned with students’ needs.